The Influence of Good Corporate Governance on Investment Risks in Banking Companies Listed on the Indonesia Stock Exchange (IDX) - Badollahi, Ismail; Masrullah, Masrullah; Angelita, Anggi; Ismawati, Ismawati (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2022)
This study explains the effect of Good Corporate Governance on Investment Risk. Good Corporate Governance indicators used in this study include: Managerial Ownership (X1), Institutional Ownership (X2), Independent Board of Commissioners (X3), Audit Committee (X4) and Investment Risk. The method used in this research is to use multiple linear regression analysis. The population of this research is banking companies listed on the Indonesia Stock Exchange (BEI) for the period 2016-2018. The research sample used purposive sampling method with predetermined criteria. The purpose of this study was to determine whether a company's good corporate governance affects investment risk. The results of this study indicate that good corporate governance includes: Managerial Ownership has a negative and insignificant effect on investment risk, Institutional Ownership has a negative and insignificant effect on Investment Risk, the Independent Board of Commissioners has a negative and significant effect on Investment Risk and the Audit Committee has a negative effect on Investment Risk